Genetic association of lipid and lipid-lowing drug targets with uterine fibroids - Mei Wu; Qiannan Lin; Siyu Li; Huiyan Wang; Wenbo Zhou (Heliyon)
Objective: Observational studies suggest that blood lipids are a risk factor for uterine fibroids (UFs) and that lipid-lowering drugs are beneficial for the treatment and prevention of UF; however, the conclusions are inconsistent. We aimed to determine the causal effects of lipids and lipid-lowering drugs on UFs using Mendelian randomization (MR). Methods: Genetic variants from genome-wide association studies (GWAS) of lipid traits and variants in genes encoding lipid-lowering drug targets were extracted, and two independent UF GWAS were set as the outcome. Their effects on UF risk and related traits were estimated using the inverse variance weighted method. Results: The MR analysis revealed that high density lipoprotein cholesterol (HDL-C, OR = 0.88, 95 % CI: 0.83–0.93, P = 3.58E-6) and triglycerides (TG, OR = 1.14, 95 % CI: 1.07–1.21, P = 6.83E-5) were protective factors and risk factors for UF, respectively. Drug-targeted MR analysis results indicated that genetically predicted inhibition of cholesteryl ester transfer protein (CETP) was associated with a lower UF risk (OR = 0.95, 95 % CI: 0.92–0.98, P = 7.83E-4), as well as reduced levels or risk of other UF-associated clinical traits, including estradiol level, excessive menstruation, abdominal and pelvic pain, myomectomy, and miscarriage. Conclusions: Our study provides evidence that HDL-C and TG levels were causally associated with UF risk. Genetically proxied CETP inhibition may have a protective effect against UF, which warrants further investigation.